Heart rate variability as a measure of autonomic regulation of cardiac activity for assessing stress and welfare in farm animals — A review - von Borell, Eberhard; Langbein, Jan; Després, Gérard; Hansen, Sven; Leterrier, Christine; Marchant, Jeremy; Marchant-Forde, Ruth; Minero, Michela; Mohr, Elmar; Prunier, Armelle; Valance, Dorothée; Veissier, Isabelle (Physiology & behavior, 2007)
Measurement of heart rate variability (HRV) is a non-invasive technique that can be used to investigate the functioning of the autonomic nervous system, especially the balance between sympathetic and vagal activity. It has been proven to be very useful in humans for both research and clinical studies concerned with cardiovascular diseases, diabetic autonomic dysfunction, hypertension and psychiatric and psychological disorders. Over the past decade, HRV has been used increasingly in animal research to analyse changes in sympathovagal balance related to diseases, psychological and environmental stressors or individual characteristics such as temperament and coping strategies. This paper discusses current and past HRV research in farm animals. First, it describes how cardiac activity is regulated and the relationships between HRV, sympathovagal balance and stress and animal welfare. Then it proceeds to outline the types of equipment and methodological approaches that have been adapted and developed to measure inter-beats intervals (IBI) and estimate HRV in farm animals. Finally, it discusses experiments and conclusions derived from the measurement of HRV in pigs, cattle, horses, sheep, goats and poultry. Emphasis has been placed on deriving recommendations for future research investigating HRV, including approaches for measuring and analysing IBI data. Data from earlier research demonstrate that HRV is a promising approach for evaluating stress and emotional states in animals. It has the potential to contribute much to our understanding and assessment of the underlying neurophysiological processes of stress responses and different welfare states in farm animals.